Dose-response study of propofol combined with two different doses of esketamine for laryngeal mask airway insertion in women undergoing hysteroscopy - Lin, Yan-Jun; Chen, Su-Li; Zheng, Xiang-Li; Yu, Shuang; Lu, Liang-Yuan (Heliyon, 2024)
To prospectively determine the median effective dose (ED50) of propofol for inhibiting a response to laryngeal mask airway (LMA) insertion when combined with different doses of esketamine in female patients. A total of 58 female patients (aged 20–60 years, ASAⅠ–Ⅱ) scheduled for elective hysteroscopy were enrolled and randomly divided into 2 groups, one of which was administered 0.2 mg/kg of esketamine (K1 group, n = 28) and the other 0.3 mg/kg of esketamine (K2 group, n = 30). The 2 groups received the corresponding doses of esketamine intravenously, followed by an intravenous injection of propofol (injection time was 30 s). The initial dose of propofol was 2 mg/kg, and the dose ratio of propofol in the adjacent patients was 0.9. If a positive reaction occurred due to LMA insertion, the dose ratio in the next patient was increased by 1 gradient; if not, the dose ratio was decreased by 1 gradient. The ED50, 95 % effective dose (ED95) and 95 % confidence interval (CI) of propofol for inhibiting a response to LMA insertion in the 2 esketamine groups were calculated using probit analysis. The ED50 of propofol for inhibiting a response to LMA insertion in female patients was 1.95 mg/kg (95 % CI, 1.82–2.08 mg/kg) in the K1 group and 1.60 mg/kg (95 % CI, 1.18–1.83 mg/kg) in the K2 group. The ED95 of propofol for inhibiting a response to LMA insertion in female patients was 2.22 mg/kg (95 % CI, 2.09–2.86 mg/kg) in the K1 group and 2.15 mg/kg (95 % CI, 1.88–3.09 mg/kg) in the K2 group. Propofol combined with 0.3 mg/kg of esketamine has low ED50 and ED95 effective doses for inhibiting an LMA insertion response in female patients undergoing hysteroscopy and surgery. There were no significant adverse effects, but the additional dose of propofol and airway pressure were significantly higher than those in the group administered 0.2 mg/kg of esketamine. Based on the results, we recommend the combination of propofol with 0.2 mg/kg esketamine for optimal conditions during LMA insertion in women undergoing hysteroscopy.